2018
DOI: 10.1200/edbk_201391
|View full text |Cite
|
Sign up to set email alerts
|

Role of Germline Genetics in Identifying Survivors at Risk for Adverse Effects of Cancer Treatment

Abstract: The growing population of cancer survivors often faces adverse effects of treatment, which have a substantial impact on morbidity and mortality. Although certain adverse effects are thought to have a significant heritable component, much work remains to be done to understand the role of germline genetic factors in the development of treatment-related toxicities. In this article, we review current understanding of genetic susceptibility to a range of adverse outcomes among cancer survivors (e.g., fibrosis, urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 124 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Cytology specimens from patients with medical history of malignancies showed significant rates of abnormalities of genes, however, no significant difference was observed compared to the cases with no medical history of malignancies. Although radiotherapy-/chemotherapy-induced gene mutation has been reported, 26,27 we observed the wide prevalence of gene mutation in endometrial cells in relatively old women. Interestingly, recent study showed that more than 50% of normal endometrium had hot-spot mutations.…”
Section: Discussionmentioning
confidence: 50%
“…Cytology specimens from patients with medical history of malignancies showed significant rates of abnormalities of genes, however, no significant difference was observed compared to the cases with no medical history of malignancies. Although radiotherapy-/chemotherapy-induced gene mutation has been reported, 26,27 we observed the wide prevalence of gene mutation in endometrial cells in relatively old women. Interestingly, recent study showed that more than 50% of normal endometrium had hot-spot mutations.…”
Section: Discussionmentioning
confidence: 50%
“…The extent to which genomic variation modifies this risk in CCS is poorly understood and is an area of active research. [17][18][19] CPS recognition is vital in helping clinical teams plan primary cancer therapy, individualize disease surveillance and follow-up and, where relevant, initiate cascade testing of at-risk relatives.…”
Section: Introductionmentioning
confidence: 99%